STUDENTS’ DIFFICULTIES IN WRITING RECOUNT TEXT THROUGH PROJECT BASED LEARNING - Nindya Citra Utami; Yanuarti Apsari (IKIP Siliwangi, 2020)
English language lessons have become compulsory secondary schools. Especially, in era of globalization writing is very important The purpose of this study is to investigate students' difficulties in writing recount text through Project Based Learning. This study used descriptive qualitative research. The data was gathered through questionaire. The questionnaire were administered to eight grade students of SMPN 3 Batujajar in the academic year of 2019/2020. The questionnaires consist of 5 statements related to aspects of writing. The data was analyzed descriptively.The result showed that most of students got difficulties in writing related to five aspect of writing, such as content (23,33%), grammar or language use (56,67%), organization (36,67%), mechanic (43,33%), and vocabulary (26,67%).